Et bofællesskab og en bevægelse: en antropologisk analyse af økosamfundsaktivisme på tværs af skalaer - Hansen, Anette Høite (Politik, 2019)
The commitment to work for a sustainable transition of society has increased greatly among grassroots in recent years. Hence, civil society has taken matter into its own hands instead of waiting for action to take place on a political and structural level. Activist movements with clear political agendas have traditionally been explored and researched as examples of civil society’s way of showing engagement. However, more recently social scientific literature has turned attention towards another kind of engagement. This type of engagement is represented by different lifestyle movements that have an interest in the practices of socalled everyday makers and practivists. This article follows this approach and explores activism from an everyday practical perspective through qualitative research studies of Danish eco-communities. Whereas studies of lifestyle movements often focus on individual sustainable practice, this article includes collective achievements where sustainable lifestyle is practiced with the purpose of making a successful community. The article shows how the (micro activist) change making collective practices that are taking place locally in eco-communities are represented by (the macro activist) networkers at a larger scale through their work for change outwards in society; on a national level in the Danish Association of Eco-communities (LØS) and on a global level in the Global Ecovillage Network (GEN). The article thus describes, how activism on different scales – practivism, microactivism, and macroactivism – are practiced in Danish eco-communities as well as in the Eco-Community Movement. The article thereby argues how these scales of activism mutually reinforce each other by ensuring that local eco-communities are liveable and that eco-community principles gain ground in ‘mainstream society’.